2014
DOI: 10.1016/j.bbadis.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue plasticity from WAT to BAT and in between

Abstract: Adipose tissue plays an essential role in regulating energy balance through its metabolic, cellular and endocrine functions. Adipose tissue has been historically classified into anabolic white adipose tissue and catabolic brown adipose tissue. An explosion of new data, however, points to the remarkable heterogeneity among the cells types that can become adipocytes, as well as the inherent metabolic plasticity of mature cells. These data indicate that targeting cellular and metabolic plasticity of adipose tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
178
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 262 publications
(323 reference statements)
3
178
0
2
Order By: Relevance
“…In fact, several (138) although not all (139) observational studies have suggested an association between high birth-weight and T2D risk in adulthood, highlighting that the possible protection associated with accelerated early growth may be somewhat transient. Even within the context of higher adipogenic and lipogenic potential in SAT, buffering capacity can be exceeded by chronic overnutrition, resulting in MUO development (140) .…”
Section: Gestationmentioning
confidence: 99%
“…In fact, several (138) although not all (139) observational studies have suggested an association between high birth-weight and T2D risk in adulthood, highlighting that the possible protection associated with accelerated early growth may be somewhat transient. Even within the context of higher adipogenic and lipogenic potential in SAT, buffering capacity can be exceeded by chronic overnutrition, resulting in MUO development (140) .…”
Section: Gestationmentioning
confidence: 99%
“…In vivo, brite adipocytes stem from progenitors or emerge by direct conversion of mature white adipocytes (22)(23)(24). Several studies have demonstrated the involvement of oxylipins in fat mass development through the modulation of white and brown/brite adipocyte differentiation and activity (25).…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue has notable plasticity throughout life (9) and is a highly active endocrine organ (10). It contains adipocytes, connective tissue matrices, nerve tissue, stromovascular cells, and immune cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…They have the ability to differentiate into numerous cell lineages, including adipogenic, osteogenic, chondrogenic, myogenic, cardiomyogenic, and neurogenic-like cell types (9,(21)(22)(23)(24)(25). They have been associated with expressing/secreting multiple important growth factors, cytokines, chemokines, and inflammatory biomarkers linked to cancer development and progression, including insulin-like growth factor (IGF), hepatocyte growth factor (HGF), TGFb1, VEGF, IL8, Bcl-2, and IL10 (26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%